2007
DOI: 10.1021/ac0711586
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Automated Analysis of Dynamic Metabolic Mixtures by NMR. Application to an Insect Venom

Abstract: Elucidation of the composition of chemical-biological samples is a main focus of systems biology and metabolomics. Due to the inherent complexity of these mixtures, reliable, efficient, and potentially automatable methods are needed to identify the underlying metabolites and natural products. Because of its rich chemical information content, nuclear magnetic resonance (NMR) spectroscopy has a unique potential for this task. Here we present a generalization and application of a recently introduced NMR data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 29 publications
4
67
0
Order By: Relevance
“…There are now numerous applications of STOCSY and closely related covariance techniques for enhanced information recovery from low dimensional NMR data sets on multiple and single samples [3][4][5][6][7][8][9][10][11][12][13] . The STOCSY approach has been applied to the structural assignment problem in a variety of NMR metabolic profiling contexts, such as deconvolution of overlapped chromatographic peaks in LC-NMR 7 , delineation of drug metabolism in molecular epidemiology studies 5 and separation of different molecular signatures in diffusion edited spectroscopy 6 .…”
Section: Introductionmentioning
confidence: 99%
“…There are now numerous applications of STOCSY and closely related covariance techniques for enhanced information recovery from low dimensional NMR data sets on multiple and single samples [3][4][5][6][7][8][9][10][11][12][13] . The STOCSY approach has been applied to the structural assignment problem in a variety of NMR metabolic profiling contexts, such as deconvolution of overlapped chromatographic peaks in LC-NMR 7 , delineation of drug metabolism in molecular epidemiology studies 5 and separation of different molecular signatures in diffusion edited spectroscopy 6 .…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Brüschweiler et al have demonstrated the acquisition of 2D NMR spectra with minimal datasets [10] as well as the use of covariance processing methods with TOCSY spectra to extract individual component spectra from a mixture. [11,12] We now report the application of covariance NMRprocessing methods to observe multistep long-range correlations in COSY spectra acquired with modest numbers of increments of the evolution period, t 1 . Generally, the observation of small, longrange homonuclear couplings in a COSY spectrum requires either the acquisition of a spectrum with large numbers of increments of the evolution period or by delaying the start of the evolution period.…”
mentioning
confidence: 99%
“…Furthermore, NMR can be used for structural elucidation and to study molecular dynamics [17][18][19][20][21][22]. Consequently, NMR is generally used as a complementary technique to mass spectrometry (MS) for the identification and quantitative analysis of the chemical composition of natural products and biological samples, such as urine [12,[23][24][25][26]. In fact, both NMR and MS have been used intensively for drug discovery from natural products [27,28], for drug assessment [29], for characterizing newly designed drugs [30,31], and for evaluating drug toxicity [32].…”
Section: Discussionmentioning
confidence: 99%